Edukasi Berbasis Theory of Planned Behavior untuk Mencegah Perilaku Seksual Berisiko pada Remaja: A Systematic Review - Lestari, Wahyu Agustin Eka; Indarwati, Retno; Krisnana, Ilya; Sudarsiwi, Neisya Pratiwindya (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Introduction: Risky sexual behavior in adolescents is behavior that arises from sexual urges, which can come from one self or from others. Theory of Planned Behavior is one of the important theories that explain the main process of adopting healthy behavior. This study aims to explain the effect of TPB-based education on risky sexual behavior in adolescents in Indonesia. Methods: Systematic review by searching four electronic databases namely Scopus, PubMed, Web of Science, and Science Direct from previous studies using qualitative research designs, cross-sectional studies, experimental studies, randomized control and trial studies, mixed method studies, quasi- experimental and published in the last 5 years (2018-2022). Results: found 8 articles as results. All of them discuss the use of the theory of planned in preventing risky sexual behavior. The text explains why TPB-based education is important, the materials provided and the supportive environment. Conclusion: The results of a systematic review show that educational programs based on the theory of planned behavior in preventing risky sexual behavior are beneficial in increasing knowledge, attitudes, subjective norms and behavior control